Access to digital technologies and the internet in higher education: validation of a diagnostic questionnaire - Pimentel, Fernando Silvio Cavalcante; da Silva, Alan Pedro; Dermeval, Diego; Rocha Ferreira, Adilson; de Sousa Pimentel, Maria Fernanda; Chalco Challco, Geiser (Debates em Educação, 2022)
This work presents the process used to validate a data collection instrument in the context of the Covid-19 pandemic. The aim was to demonstrate the reliability of a questionnaire about access to digital technologies and the Internet by university students. The questionnaire construction process consisted of two stages: items were initially developed based on the objectives indicated by the Working Group, mapping the items related to “Technical Information” (INF) and “Experience” (EXP) with Digital Technologies in Education. In the second stage, the items were adjusted and divide into different sections in order to provide the respondent with one context at a time. The validity performed in the construction of the instrument indicates that the questionnaire developed is adequate to measure the latent factors of technical information. Although there was no complete invariance of the instrument for all groups of respondents, the validation conducted indicates that the instrument is relatively good for comparing the mean of latent factors in most groups.